Violent delights, violent ends : sex, race, & honor in colonial Cartagena de Indias - Germeten, Nicole von (University of New Mexico Press, 2013)
"This study of sexuality in seventeenth-century Latin America takes the reader beneath the surface of daily life in a colonial city. Cartagena was an important Spanish port and the site of an Inquisition high court, a slave market, a leper colony, a military base, and a prison colony--colonial institutions that imposed order by enforcing Catholicism, cultural and religious boundaries, and prevailing race and gender hierarchies. The city was also simmering with illegal activity, from contraband trade to prostitution to heretical religious practices. Nicole von Germeten's research uncovers scandalous stories drawn from archival research in Inquisition cases, criminal records, wills, and other legal documents. The stories focus largely on sexual agency and honor: an insult directed at a married woman causes a deadly street battle; a young doña uses sex to manipulate a lustful, corrupt inquisitor. Scandals like these illustrate the central thesis of this book: women in colonial Cartagena de Indias took control of their own sex lives and used sex and rhetoric connected to sexuality to plead their cases when they had to negotiate with colonial bureaucrats"--